Black beauty - Sewell, Anna. (London : Scholastic Books, 2013)
A horse in nineteenth-century England recounts his experiences with both good and bad masters. As a young colt, Black Beauty gallops in the fresh green meadows with his beloved mother, Duchess, and their kind master. But when his owners are forced to sell him he swaps a life of freedom and happiness for one of work and toil. Black Beauty has an unbreakable spirit and a strong will, but is it enough to survive ...?
CONTENTS: My early home -- Hunt -- My breaking in -- Birtwick park -- Fair start -- Liberty -- Ginger -- Ginger's story continued -- Merrylegs -- Talk in the orchard -- Plain speaking -- Stormy day -- Devil's trade mark -- James Howard -- Old ostler -- Fire -- John Manly's talk -- Going for the doctor -- Only ignorance -- Joe Green -- Parting -- Earshall -- Strike for liberty -- Lady Anne -- Reuben Smith -- How it ended -- Ruined and going down-hill -- Job-horse and his drivers -- Cockneys -- Thief -- Humbug -- Horse fair -- London cab horse -- Old war horse -- Jerry Barker -- Sunday cab -- Golden rule -- Dolly and the real gentleman -- Seedy Sam -- Poor Ginger -- Butcher -- Election -- Friend in need -- Old captain and his successor -- Jerry's new year -- Jakes and the lady -- Hard times -- Farmer Thoroughgood and his grandson Willie -- My last home.
Keywords: Black Beauty (Fictitious character); Great Britain -- History -- 19th century -- Fiction; Horses -- Fiction